(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
This paper deals with experimental researh of compressed concrete filled tubular elements with separable joints. The purpose of experimental research of compressed concrete filled tubular elements with separable joints was to obtain data of behavior of separable joints configuration on tubular elements bearing capacity and nature of work. Also stressstrain state and bearing capacity of different separable joints were compared for creating the best design of separable joint in compressed tubular elements. Common to all experimental samples was design of concrete filled tubular element: not reinforced steel pipe made of steel grade S345, pipe length of 800 mm, pipe diameter of 102 mm, pipe wall thickness of 4 mm. The samples had bolt connections with bolts 5N6 made of steel grade 5.8. The noncentral compressed tubular elements had console for creating eccentricity of applied load 27 and 54 mm. The main features of samples deformation and nature of work were that none sample completely not destroyed in the conventional sense of the word, especially not occurred break of steel pipe shells, but the most of the samples were characterized by the formation of corrugation in near support zone and appearance of Lyuders – Chernov lines in compressed zone of tubular element. It is also worth noting that bolts weren’t cutting and destruction wasn`t happened in the area of separable joints. When the eccentricity of load application was changed we were seen the great change of compressed concrete filled tubular elements bearing capacity with increasing of eccentricity from 0 to 0.5 diameter maximum bearing capacity depending on the type of design of the joint decreased 1.5 – 3 times. The samples of TBM series revealed the largest bearing capacity at maximum eccentricity of load application. The value of N2 for sample of TBR and TBF series was almost identical 13% less than the sample series TBM but significantly higher (33%) in comparison with concrete filled tubular elements without joints. N2 to N1 ratio ranged from 1.02 for noncentral compressed tubular elements without joint to 1.47 for concrete filled tubular elements with separable joint made of steel coupling. The average ratio for the most samples was amounted to 1.2 – 1.3 which indicating the durability of this samples and the bearing capacity reserves even after reaching samples N1. The most effective design of concrete filled steel tubular elements with separable joint according to experimental research was a series of TBM (tubular elements with separable joint made of steel coupling). Samples of the given series had the highest bearing capacity, the largest efficiency coefficients and the smallest materials costs, indicating the high efficiency design of the given type. Lowest indicators of bearing capacity and work efficiency compared to other samples appeared in a series of TBF. The samples of TBR series had the highest material cost. Keywords: concrete filled tubular structure, separable joints, stress-strain state.